Adopting International Public Sector Accounting Standards: a challenge for modernizing and harmonizing public sector accounting. (December 2016) - Brusca, Isabel; Martínez, Juan Carlos
The International Public Sector Accounting Standards have been seen as a path towards the modernization of governmental accounting, and many countries have made efforts to adopt them. The purpose of this article is to analyse the stimuli and barriers to the adoption of International Public Sector Accounting Standards, as well as their main benefits, using a structural equation model. The research methodology is based on a questionnaire sent to American and European Union countries that has been used to construct a structural model, and our results show that comparability and modernization are direct benefits of International Public Sector Accounting Standards implementation, and that both adopter and non-adopter countries value these positive impacts. This justifies the process of harmonization that the European Commission recently started. Points for practitioners: The analysis of the impact of International Public Sector Accounting Standards in the international context shows to what extent the adoption of International Public Sector Accounting Standards are useful for modernizing governmental accounting and achieving accounting comparability. Describing the experience of countries that have adopted International Public Sector Accounting Standards can help practitioners and professionals who participate in modernizing accounting systems, such as the European Union. Many countries are now moving towards International Public Sector Accounting Standards and the experiences of pioneer countries can serve as a learning process. This article shows that introducing International Public Sector Accounting Standards can have many advantages in practice and that countries that have implemented these standards consider that they allow an increase in transparency and accountability.